Relationship Between Strategic Capabilities and Competitive Advantage in the Kenyan Banking Sector - Kamau, James Gathogo; Senaji, Thomas A.; Eng, R.; Nzioki, Susan (IPRJB, 2019)
Purpose: The Commercial banks operating in Kenya are experiencing a faster pace of change characterized by customers’ sophistication, strict regulation and supervision, technology advancement, liberalization of banking license leading to rapid internationalization. Thus this study sought to link strategic capabilities and competitive advantage in the Kenyan banking sector. Methodology: The study is anchored on the McKinsey 7S Framework Model, the Resource Based View, the dynamic capability Theory and the Market Power Theory. A positivist research philosophy was adopted for the study. Focusing on 39 operational commercial banks in Kenya, a descriptive survey design was adopted. Primary data was collected and applied in the study. The relationship between the variables was tested using ordinary east square regression model. On the other hand, the moderating effects of Central Bank of Kenya regulations was also tested using the moderated multiple regression model. Findings: The study findings revealed that strategic capabilities that is knowledge management capability, information technology capability, operational adjustment agility and market capitalizing agility have a positive and significant effect on competitive advantage of commercial banks in Kenya. Furthermore, central bank regulations have a significant moderating effect on the relationship between strategic capabilities and competitive advantage of commercial banks in Kenya. Unique contribution to theory, practice and policy: The study findings led to the recommendation that the commercial banks should enhance the practices that improves their strategic capabilities. On the other hand, the central bank of Kenya on the other hand should aim to come up with favorable policies which won’t hurt the operations of the commercial banks.
Keywords: Information Technology Capability; Knowledge Management Capability; organizational adjustment agility; market capitalizing agility; Central Bank Regulations and Competitive Advantage